Semarga Marriage Practices in the Alas Tribe in Lawe Bulan District Southeast Aceh Regency (Jurnal Adabiya, 2025)
The main focus of this paper is to review the practice of marriage since it is a marriage practice that is prohibited in the customary rules of the Alas tribe community. This marriage procession is almost the semarga as other marriage customs, only before the wedding, the family first pays a customary fine. The purpose of this study is to find out the practice of clan marriage, clan marriage factors and public view on clan marriage in Lawe Bulan district, Southeast Aceh Regency. This study uses a qualitative type of research. The research instrument used are observation, interview and documentation. Data analysis techniques are in the form of data reduction, data presentation and verification/conclusion. This study found that the implementation of marriage since giving a sign (sakhi pinang) asking for blessings, (nganpeken) determining the marriage schedule (mahan janji), paying a dowry (ngatatken mas), distributing invitations (mebagah), a three-day party (jagai), ijab qabul (marriage contract) attended by guardians and witnesses, escorting the bride and groom (nakhuh), ngembakh and nangkuh. The causes of intermarriage are lack of understanding of the customs of the Alas tribe, lack of insight, low education, lower middle class economy, social media influence, establishing a dating relationship, social strata, being caught alone in a lonely place and getting pregnant out of wedlock. The community's view of intermarriage is generally disagreeable, because in addition to violating customs and not being good for their offspring, such as physical disabilities, mental weakness and idiots. ABSTRAKFokus utama tulisan ini adalah meninjau praktik perkawinan semarga merupakan sebuah praktik pernikahan yang dilarang dalam aturan adat masyarakat suku alas. Prosesi perkawinan ini hampir sama dengan adat perkawinan lainnya hanya saja sebelum melangsungkan pernikahan pihak keluarga terlebih dulu membayar denda adat. Tujuan penelitian ini untuk mengetahui praktik perkawinan semarga, faktor perkawinan semarga dan pandangan masyarakat terhadap perkawinan semarga di kecamatan Lawe Bulan Kabupaten Aceh Tenggara. Penelitian ini menggunakan jenis penelitian kualitatif. Instrumen penelitian yang digunakan adalah observasi, wawancara dan dokumentasi. Teknik analis data berupa reduksi data, penyajian data dan verifikasi/kesimpulan. Penelitian ini mendapat hasil bahwa pelaksanan perkawinan semarga memberi tanda (sakhi pinang) meminta restu, (nganpeken) menentukan jadwal nikah (mahan janji), mengatar mahar (ngatatken mas), menyebarkan undangan (mebagah), pesta tiga hari (jagai), ijab qabul (akad nikah) dihadiri oleh wali dan saksi, mengantar pengantin perempuan dan pengantin lelaki (nakhuh), ngembakh dan nangkuh. Penyebab perkawinan semarga kurang pemahaman tentang adat suku alas, kurang wawasan, pendidikan rendah, ekonomi menengah ke bawah, pengaruh media sosial, menjalin hubungan pacaran, strata sosial, tertangkap berduaan ditempat sepi dan hamil diluar nikah. Pandangan masyarakat terhadap perkawinan semarga secara umum mereka tidak setuju, karena selain melanggar adat dan tidak baik bagi keturunannya seperti cacat fisik, lemah mental dan idiot.
Keywords: Semarga Marriage Practice; Alas Tribe; Lawe Bulan; Southeast Aceh.